Analysis of Maqāshid Sharī’a on Substitute Heir in Compilation of Islamic Law (KHI) - Saniah, Nur; Yuslem, Nawir; Matsum, Hasan (Universitas Islam Negeri Raden Intan Lampung, 2023)
This study analyzes the application of maqāshid sharī’a (objectives of shari'a) regarding substitute heirs as outlined in article 185 paragraphs 1 and 2 of the Compilation of Islamic Laws the research aims to find out the philosophical basis of maqāshid sharī’a regarding the importance of giving inheritance to substitute heirs. This research is a normative legal research that uses a philosophical approach. Data were collected using literature techniques, then analyzed descriptively qualitatively through maqāshid sharī’a theories. This study shows that the determination of inheritance for substitute heirs in Article 185 is important to realize because it contains many maslahah (benefits) both sociologically and psychologically. The philosophical foundation of maqāshid sharī’a in inheritance for substitute heirs is not only limited to protecting assets (hifzd al-māl) but also to improving their quality of life (tanmiyah al-nasl wa al-māl). Substitute heirs are not enough just to be given assets, they also need care and affection from their extended family. Viewed from the maslahah position, giving inheritance to substitute heirs to improve their quality of life is included as maslahah dharūriyah (urgent needs).